Prevalence of Celiac Disease Among First-degree Relatives of Patients With Celiac Disease - Dogan, Yasar; Yildirmaz, Serap; Ozercan, Ibrahim Hanifi (Lippincott Williams & Wilkins, 2012)
Objectives: Celiac disease, an autoimmune enteropathy that affects the proximal small intestine, is characteristically seen in people who have a genetic susceptibility to gluten sensitivity. Celiac patients' first-degree relatives are more at risk of acquiring the disease. The objective of the present study was consequently to determine the prevalence of celiac disease in a group of first-degree relatives of our patients with celiac disease. Methods: First-degree relatives of 195 patients with celiac disease attending a gastroenterology unit underwent serologic screening. Antitissue transglutaminase (anti-tTG) immunoglobulin A (IgA) and total serum IgA tests were used for first-level screening. Duodenal biopsy was recommended to subjects showing positive results to anti-tTG IgA testing. Biopsy samples were obtained by endoscopy, and biopsy specimens were evaluated and classified according to Marsh classification. Results: Positive anti-tTG IgA was found in 46 first-degree relatives (9.5%), whereas serum IgA levels were normal. Of 46 serology-positive relatives, 34 agreed to the endoscopy procedure. Histological changes characteristic of celiac disease were found in 23 subjects. The prevalence of celiac disease among the first-degree relatives was found to be at least 4.8%. Of 34 subjects that underwent biopsy, 11 were evaluated as Marsh 0, 5 as Marsh 1, 4 as Marsh 2, 12 as Marsh 3, and 2 as Marsh 4. Of the biopsy-positive subjects, 3 were mothers, 1 was a father, and 19 were siblings. Conclusions: The present study identified 23 undiagnosed cases of celiac disease among 484 first-degree relatives of 195 patients with celiac disease, confirming the high prevalence (4.8%) of the disease in this specific group. It is suggested that an extensive screening policy be mandatory for these subjects.
Keywords: celiac disease; first-degree relatives; prevalence; tissue transglutaminase immunoglobulin A